CB5712809, a novel Keap1 inhibitor upregulates SQSTM1/p62 mediated Nrf2 activation to induce cell death in colon cancer cells - Ayed A. Dera; Majed Al Fayi (Discover Oncology)
Abstract Background The study focuses on Keap1, a key regulator of the Nrf2 pathway, critical for tumor cell regulation. Recent crystallographic insights into Keap1's structure highlight its functional domains and ligand-binding sites, offering opportunities for targeted drug discovery. The aim is to identify small molecules with high affinity for Keap1 to modulate Keap1, SQSTM1/p62, and Nrf2 functions in colorectal cancer (CRC) cells. Methods A high-throughput virtual screening approach was used to screen the ChemBridge small library against the Keap1 protein. Atomistic Molecular Dynamics (MD) simulations were conducted using GROMACS, along with Gibbs binding free energy estimations. HCT116 and Caco-2 cells were used to determine anti-proliferation. Flow cytometry was used to evaluate target + inhibition in HCT116 and Caco-2 cells. Results The small molecule CB5712809 demonstrated stable interactions with Keap1, supported by molecular dynamics simulations and MM-PBSA analysis. It suppressed the growth of HCT116 and Caco-2 CRC cells with GI50 values of 40.07 nM and 102.80 nM, respectively. Flow cytometry revealed G2/M cell cycle arrest, along with decreased Keap1 levels and increased SQSTM1/p62 and Nrf2 expression, highlighting its potential as a Keap1 modulator. Conclusion Results of this study provide a basis for further experimental validation to develop CB5712809 as a Keap1 targeted chemotherapeutic against CRC. Graphical Abstract